Application of Quasisubordination to Certain Classes of Meromorphic Functions. (14th October 2020) - Shah, Syed Ghoos Ali; Hussain, Saqib; Rasheed, Akhter; Shareef, Zahid; Darus, Maslina
Abstract : Inequalities play a fundamental role in many branches of mathematics and particularly in real analysis. By using inequalities, we can find extrema, point of inflection, and monotonic behavior of real functions. Subordination and quasisubordination are important tools used in complex analysis as an alternate of inequalities. In this article, we introduce and systematically study certain new classes of meromorphic functions using quasisubordination and Bessel function. We explore various inequalities related with the famous Fekete-Szego inequality. We also point out a number of important corollaries.